The Taxation Knowledge, Tax Rate and Awareness Toward SMEs Taxpayer Compliance in Bekasi City - Ratih Kumala Ratih; Anisah Anisah (Economics and Digital Business Review, 2021)
The purpose of this study was to determine the effect of tax knowledge, tax rates and taxpayer awareness on the compliance of individual taxpayers of SMEs in Bekasi City. This research uses a descriptive approach. Data collection was carried out by means of a questionnaire. Data analysis techniques used classical assumption test, partial test (t test) simultaneous test (f test) and determination coefficient (R2).The results of this study identify that the tax knowledge variable has a positive and significant effect on individual SMEs taxpayer compliance. Tax rate variables have a positive and significant effect on SMEs taxpayer compliance and taxpayer awareness variables have a positive and significant effect on SMEs taxpayer compliance.